Hydration and glass transition of hybrid non-isocyanate polyurethanes with POSS inclusions. (22nd June 2022) - Raftopoulos, Konstantinos N.; Łukaszewska, Izabela; Bujalance Calduch, Carlos; Stachak, Piotr; Lalik, Sebastian; Hebda, Edyta; Marzec, Monika; Pielichowski, Krzysztof
Abstract: A non-isocyanate poly (hydroxyurethane) network was synthesized by reaction of a tricyclic carbonate compound with diamines. The system was modified by two types of Polyhedral Oligomeric Silsesquioxane (POSS) molecules, one retaining the crosslinked nature of the system, and another effectively loosening it. We studied water absorption as a function of environmental humidity and observed that all systems are extremely hydrophilic, absorbing up to 65% of water when exposed to 97% environmental humidity. In parallel, using differential scanning calorimetry and dielectric spectroscopy, we studied the effects of POSS and the significant plasticization caused by absorbed water on the glass transition and charge mobility. In dry materials, crosslinking POSS seems to reinforce the matrix and at least initially slow down mobility while the opposite effect is observed for the moiety that loosens the network. Both POSS inhibit plasticization, both indirectly by inhibiting water absorption, and directly, by stiffening the network, especially in the case of crosslinking POSS. Graphical abstract: Image 1 Highlights: Non-isocyanate poly (hydroxyurethane)s networks are very hydrophilic polymers. Absorption of aater causes extreme reduction of T g . POSS affect glass transition of these networks in ways dependent on the topology. POSS affect the water absorbing capacity of the networks.